?La Grande Boucle?: Determinants of Success at the Tour de France - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Cycling has not been analyzed intensively in the economics of sports literature. This paper reports empirical evidence of individuals' performances in the 2004 "Tour de France". We investigate different performances such as total ranking, mountain ranking, time trial rankings as dependent variables and search for factors that shape riders' performances. The results show that riders who were successful in previous Tours perform better than other participants. Team leaders are more successful, and a lower body-mass index leads to a better performance. We also observe differences among the participating countries. Finally, the results suggest that riders' performances are influenced by their teammates.
Keywords: L83; 330; sport; cycling tour; Tour de France; team effect